Isolation and Cr(VI) reduction characteristics of quinone respiration in Mangrovibacter plantisponsor strain CR1. (18th August 2015) - Lian, Jing; Li, Zifu; Xu, Zhifang; Guo, Jianbo; Hu, Zhenzhen; Guo, Yankai; Li, Min; Yang, Jingliang
Abstract: A Cr(VI)‐reducing Mangrovibacter plantisponsor strain, CR1, was isolated from tannery effluent sludge and had quinone respiration characteristics. Its chromate (CrO4 2− ) resistance, quinone respiration characteristics, and Cr(VI) reduction efficiencies were evaluated in detail. Strain CR1 exhibited a high Cr(VI) resistance with a minimal inhibitory concentration (MIC) of 32 mM in LB medium, and its quinone respiration could occur when an electron donor and strain CR1 both existed in the reaction system. Cr(VI) reduction by strain CR1 was significantly enhanced by a factor of 0.4–4.3 with five different quinone compounds: anthraquinone‐2, 7‐disulfonate, anthraquinone‐1‐sulfonate, anthraquinone‐2‐sulfonate (AQS), anthraquinone‐2, 6‐disulfonate, and anthraquinone‐1, 5‐disulfonate. AQS was the best electron shuttle among them, and the greatest enhancement to the Cr(VI) bio‐reduction was achieved with 0.96 mM AQS. The correlation between the reaction constant k (mg Cr(VI) g −1 dry cell weight H −1 ) and thermodynamic temperature T (K) was expressed as an Arrhenius equation ln k = − 7662.9 / T + 27.931 ( R 2 = 0.9486 ) ; the activation energy E a was 63.71 kJ mol −1, and the pre‐exponential factor A was 1.35 × 10 12 mg Cr(VI) g −1 dry cell weight H −1 . During the Cr(VI) reduction process, the pH tended to become neutral, and the oxidation–reduction potential decreased to −440 mV. The efficient reduction of Cr(VI) mediated by a quinone respiration strain shows potential for the rapid anaerobic removal of Cr(VI).